Lithium ion battery
By designing the structure of the negative electrode sheet in a lithium-ion battery, controlling the spacing and expansion of graphite particles, the problem of poor circulation performance of natural graphite is solved, and the high energy density and good circulation performance of the battery are achieved.
Patent Information
- Application Number
- CN202411914792.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-28
AI Technical Summary
The existing lithium-ion battery negative electrode material natural graphite has poor charging and discharge cycle performance, which limits its application space, and the advantages of high energy consumption and low cost in the production process have not been fully utilized.
By designing the negative electrode sheet of the lithium-ion battery, including the negative current collector and the negative active material layer, the distance between the negative active material layer and the current collector is less than 0.5 μm and the spacing between adjacent graphite particles is less than 2 μm, the expansion and side reaction of graphite particles are controlled and the circulation performance is improved.
It achieves a better charging and discharge cycle life and high energy density of lithium-ion batteries, inhibits the expansion of graphite particles and the consumption of electrolyte, and improves the circulation performance of the battery.
Smart Images

Figure CN119725680A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrochemical devices, and in particular to a lithium ion battery. Background Art
[0002] Lithium-ion batteries are highly recognized by consumers for their small size, high energy density, stable charge and discharge cycles and no memory effect. The negative active material materials used in the negative electrode of lithium-ion batteries include artificial graphite, natural graphite, mesophase carbon microspheres, hard carbon, soft carbon and silicon. The raw materials of artificial graphite come from petroleum coke and petroleum needle coke, which are byproducts of the petrochemical industry, or from coal-based needle coke and coal-based asphalt coke, which are byproducts of the coal chemical industry. These are non-renewable energy sources and cannot be used for a long time. In addition, the production process of artificial graphite must be graphitized (heat treatment temperature 2500-3300℃), which consumes a lot of energy and does not meet the requirements of the low-carbon economic development advocated by the country. The energy density of mesophase carbon microsphere negative electrode materials is very low (low capacity and compaction) and its process is complex, and the yield is low, which leads to high cost and is difficult to apply. As negative active material materials, hard carbon and soft carbon have low energy density (low first efficiency and compaction) and cannot be widely used. Silicon negative electrode has high capacity, but has large problems of first efficiency and cycle expansion, and is currently less used.
[0003] Natural graphite has high capacity and compaction. The raw material comes from graphite minerals, which are abundant in resources and have a high degree of graphitization. No graphitization process is performed during the processing, so its energy consumption and cost are low. It has high energy density and is widely used.
[0004] However, natural graphite is obtained by crushing and spheroidizing flake graphite, which results in many defects inside the particles due to the curling of flake graphite sheets. These defects result in poor battery charge and discharge cycle performance when it is used as a negative electrode active material for lithium-ion batteries, thereby limiting its use. Only by solving the problem of poor cycle performance can its advantages of high energy density and low cost be brought into play. Summary of the invention
[0005] The purpose of the present invention is to overcome the above problems existing in the prior art and provide a lithium ion battery having a good charge and discharge cycle life and a high energy density.
[0006] In order to achieve the above object, the present invention provides a lithium ion battery, the lithium ion battery comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, the negative electrode sheet comprising a negative electrode current collector and a negative electrode active material layer located on at least one side of the negative electrode current collector, the negative electrode active material layer comprising a negative electrode active material, and the negative electrode active material comprising graphite particles;
[0007] When the lithium-ion battery is in a charged state of 0% SOC, the distance between the negative electrode active material layer and the negative electrode current collector is less than 0.5 μm, and the distance between adjacent graphite particles is less than 2 μm.
[0008] In the present invention, when the lithium-ion battery is in a charged state of 0% SOC, the distance between the graphite particles and the current collector, and the distance between the graphite particles are within the above range, which means that the degree of solvent co-embedding between the graphite particles in the negative electrode sheet and the solvent in the electrolyte is low. On the one hand, the expansion of the graphite particles is controlled within a relatively low range, and on the other hand, the side reaction between the graphite particles and the electrolyte is suppressed, so that the battery can maintain a relatively high energy density while obtaining the effect of improving the cycle performance of the lithium-ion battery.
[0009] The endpoints and any values of the range disclosed in this article are not limited to the precise range or value, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article. Herein, in the absence of special instructions, data ranges include endpoints. BRIEF DESCRIPTION OF THE DRAWINGS
[0010] Figure 1 Shown is a SEM image of the cross section of the negative electrode sheet of the lithium ion battery prepared in Example 1.
[0011] Figure 2 Shown is a graph of the capacity retention rate of the cylindrical steel shell battery prepared in Example 1 after 500 high-temperature cycles. DETAILED DESCRIPTION
[0012] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0013] Unless otherwise defined, all scientific and technical terms used in the present invention have the same meanings as commonly understood by one of ordinary skill in the art to which the present invention relates.
[0014] The present invention provides a lithium-ion battery, the lithium-ion battery comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, the negative electrode sheet comprising a negative electrode current collector and a negative electrode active material layer located on at least one side of the negative electrode current collector, the negative electrode active material layer comprising a negative electrode active material, and the negative electrode active material comprising graphite particles;
[0015] When the lithium-ion battery is in a charged state of 0% SOC, the spacing between the negative electrode active material layer and the negative electrode current collector is less than 0.5 μm (for example, 0.5 μm, 0.4 μm, 0.3 μm, 0.2 μm, 0.1 μm, 0.05 μm, 0.01 μm, 0 μm), and the spacing between adjacent graphite particles is less than 2 μm (for example, 2 μm, 1.5 μm, 1 μm, 0.5 μm, 0.1 μm, 0.05 μm, 0.01 μm, 0 μm).
[0016] SOC refers to the state of charge of the battery, which indicates the current charge level of the battery, that is, the proportion of the electrical energy stored in the battery to its total capacity.
[0017] The method for measuring the distance between the negative electrode active material layer and the negative electrode current collector includes: taking a lithium ion battery in a charged state of 0% SOC, splitting the negative electrode sheet, and then selecting a region with a length*width size of 150μm*120μm in a cross-sectional scanning electron microscope image of the negative electrode sheet after argon ion beam cutting (the electron microscope magnification is 1000 times), evenly taking 5 points in the width direction, measuring the distance between the negative electrode active material layer and the current collector, and then taking the average of these 5 values as the distance between the negative electrode active material layer and the negative electrode current collector.
[0018] The method for measuring the distance between adjacent graphite particles includes: taking a lithium-ion battery in a charged state of 0% SOC, splitting the negative electrode sheet, and then taking the distance between the edge of the graphite particle and the adjacent graphite particle at 10 locations along the same spacing in the cross-sectional scanning electron microscope image of the negative electrode sheet after argon ion beam cutting (the electron microscope magnification is 1000 times), and taking the average value of the distance as the distance between adjacent graphite particles.
[0019] In some embodiments, the peak intensity ratio of Id to Ig of the negative electrode active material is Id / Ig of 0.1-0.5, such as 0.1, 0.2, 0.3, 0.4, or 0.5.
[0020] The values of Id and Ig can be tested by Raman spectroscopy, which includes: using a HORIBA HR800 in situ microscopic laser confocal Raman spectrometer, which is equipped with four lasers with wavelengths of 325nm, 532nm, 633nm, and 785nm, and a Raman shift range of 100-4000cm -1 The peak position of D peak is 1300-1400cm -1 The diffraction intensity of the D peak is recorded as Id, and the peak position of the G peak is 1550-1650cm -1 , the diffraction intensity of the G peak is recorded as Ig.
[0021] In some embodiments, the degree of graphitization of the negative electrode active material is 94.5%-98.5%, such as 94.5%, 95%, 95.5%, 96%, 96.5%, 97%, 97.5%, 98%, 98.5%.
[0022] In some embodiments, the average length La of the a-axis growth of the microcrystals of the negative electrode active material is For example
[0023] XRD can be used to test the graphitization degree and La. The formula for calculating the graphitization degree is G = (3.44-d) / 0.0086*100%. The Bragg formula 2dsinθ = nλ can be used to calculate d, where d is the graphite interlayer spacing of D002, θ is the diffraction angle corresponding to the D002 peak, λ is the wavelength of the incident wave, and n is the reflection order. The average length La of the graphite microcrystals growing in the a-axis direction of the negative electrode active material can be calculated by software fitting of the XRD image.
[0024] In some embodiments, the particle size Dv50 of the negative electrode active material is 5-25μm (for example, 5μm, 10μm, 15μm, 20μm, 25μm), 0.35≤Dv10 / Dv90≤0.45 (for example, 0.35, 0.36, 0.37, 0.38, 0.39, 0.4, 0.41, 0.42, 0.43, 0.44, 0.45), and Dn10≥3μm (for example, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm).
[0025] If the proportion of small-particle graphite particles is large, the consumption of electrolyte will be accelerated, resulting in deterioration of cycle performance due to the large number of surface defects and high reaction activity of small-particle graphite. Controlling the particle size distribution of graphite particles to present a relatively concentrated trend and reducing the number of small particles in the particles can control the charging expansion of graphite particles within a smaller range, thereby improving the cycle performance of the battery.
[0026] In the present invention, DvN (such as Dv10, Dv50, Dv90) refers to the particle size corresponding to the cumulative volume particle size distribution percentage of a sample reaching N%. Dn10 refers to the particle size corresponding to the cumulative number particle size distribution percentage in the sample reaching 10%. The particle size can be measured by conventional methods in the art, such as laser particle size method, and the instrument model used is Mastersizer 3000 laser particle size analyzer.
[0027] In some embodiments, the particle size Dv10 of the negative electrode active material is 5-15 μm, such as 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, and 15 μm.
[0028] In some embodiments, the particle size Dv90 of the negative electrode active material is 10-40 μm, such as 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, or 40 μm.
[0029] In some embodiments, the BET specific surface area of the negative electrode active material is 2-8 m 2 / g, for example 2m 2 / g, 3m 2 / g, 4m 2 / g, 5m 2 / g, 6m 2 / g, 7m 2 / g, 8m 2 / g.
[0030] The specific surface area test was conducted using the American Micromeritics TriStar II 3020Plus high-throughput specific surface area and pore size analyzer.
[0031] In some embodiments, the tap density of the negative electrode active material is 0.9-1.2 g / cm 3 , for example 0.9 g / cm 3 , 1g / cm 3 , 1.1g / cm 3 , 1.2g / cm 3 .
[0032] The tap density test was conducted using a tap density meter from Quantachrome Instruments, Inc., USA, and the equipment model was Autotap.
[0033] In some embodiments, the sphericity of the negative electrode active material is 0.5-0.95, for example, 0.5, 0.6, 0.7, 0.8, 0.9 or 0.95. By adjusting the sphericity of the negative electrode active material, a negative electrode active material with a high tap density can be obtained, thereby increasing the energy density of the battery.
[0034] In some embodiments, the oil absorption value of the negative electrode active material is 10-40ml / 100g, such as 10ml / 100g, 15ml / 100g, 20ml / 100g, 25ml / 100g, 30ml / 100g, 35ml / 100g, and 40ml / 100g. The oil absorption value measures the rate at which the surface of the negative electrode active material absorbs the electrolyte. A large oil absorption value indicates a strong affinity for the electrolyte, which is unfavorable for negative electrode active materials with graphite as an active ingredient, and will cause the electrolyte to penetrate and erode the layered structure of the graphite. A lower oil absorption value can prevent the structure of the graphite from being destroyed, thereby preventing the negative electrode active material from being eroded by the electrolyte and improving the cycle capacity.
[0035] The sphericity test was conducted using a Japanese Mitutoyo roundness tester, model RA-H5200CNC. The oil absorption value was tested using a Luxembourg DABS-H New-Oil Absorption Value Tester.
[0036] In some embodiments, the graphite particles include natural graphite and amorphous carbon coated on the surface of the natural graphite.
[0037] The surface is coated with amorphous carbon material, which allows the carbon material to form a hard shell on the surface of natural graphite. This shell can inhibit its expansion during charging, while preventing the electrolyte from entering the interior of the graphite particles and corroding the graphite flakes, thereby improving the cycle capacity.
[0038] In the present invention, natural graphite refers to a product obtained by processing a natural graphite raw material (such as natural flake graphite) as a raw material. The processing method of the natural graphite can be a conventional method in the art, including but not limited to crushing, spheroidization, purification, etc. The amorphous carbon can be obtained by mixing the processed natural graphite with a carbon-based material (such as asphalt, biomass, phenolic resin, high molecular polymer, etc.) and then carbonizing it, and those skilled in the art can prepare it according to conventional methods in the art.
[0039] In some embodiments, the content of amorphous carbon in the negative electrode active material is 1-10wt%, such as 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt%, preferably 3-7wt%.
[0040] In some embodiments, the content of the graphite particles in the negative electrode active material is greater than 90wt%, such as 90wt%, 91wt%, 92wt%, 93wt%, 94wt%, 95wt%, 96wt%, 97wt%, 98wt%, 99wt%, or 100wt%.
[0041] In some embodiments, the compaction density of the negative electrode sheet is 1.1-1.5 g / cm3 , for example, 1.1 g / cm 3 , 1.2g / cm 3 , 1.3g / cm 3 , 1.4g / cm 3 or 1.5g / cm 3 .
[0042] In some embodiments, in the XRD pattern of the negative electrode sheet, the (004) crystal plane diffraction peak intensity D 004 The diffraction peak intensity D 110 Ratio D 004 / D 110 It is 7-25, for example, 7, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25.
[0043] XRD using Thermo Scientific TM ARL TM EQUINOX Pro vertical X-ray diffractometer test, the diffraction angle range is 10-90°.
[0044] In some embodiments, the peel strength of the negative electrode sheet is 10-25 N / m, such as 10 N / m, 15 N / m, 20 N / m, 25 N / m.
[0045] The negative electrode sheet peel strength refers to the peeling force of the negative electrode active material layer from the negative electrode current collector. The negative electrode sheet peel strength is tested using the general single-column material testing machine of AMETEK STC, model LLOYD (Lloyd) LS Plus series. The negative electrode sheet has a high peeling force to prevent the negative electrode particles from falling off the current collector and improve the battery cycle performance.
[0046] In some embodiments, the thickness of the single-sided negative electrode active material layer is 30-100 μm, such as 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 85 μm, or 100 μm.
[0047] In some embodiments, the negative electrode active material layer further includes a negative electrode conductor and a negative electrode binder. The negative electrode conductor, for example, includes at least one of conductive carbon black, acetylene black, Ketjen black, conductive graphite, graphene, conductive carbon fiber, and carbon nanotubes (including at least one of single-walled carbon nanotubes and multi-walled carbon nanotubes). The negative electrode binder may include a binder conventionally used in the art, for example, including at least one of polyacrylic acid, sodium polyacrylate, potassium polyacrylate, lithium polyacrylate, polyvinyl alcohol, carboxymethyl cellulose, sodium carboxymethyl cellulose, polyimide, polyamide-imide, polyvinylidene fluoride, styrene-butadiene rubber, polytetrafluoroethylene, and polyethylene oxide.
[0048] In the present invention, based on the total mass of the negative electrode active material layer, the content of the negative electrode active material is 80%-99.8% (for example, 80%, 82%, 84%, 86%, 88%, 90%, 92%, 94%, 96%, 98%, 99% or 99.8%), the content of the negative electrode conductor is 0.1%-10% (for example, 10%, 9%, 8%, 7%, 6%, 5%, 4%, 3%, 2%, 1%, 0.5% or 0.1%), and the content of the negative electrode binder is 0.1%-10% (for example, 10%, 9%, 8%, 7%, 6%, 5%, 4%, 3%, 2%, 1%, 0.5% or 0.1%).
[0049] In some embodiments, the negative electrode current collector is at least one of copper foil, chromium foil, nickel foil, and titanium foil.
[0050] In some embodiments, the electrolyte includes vinylene carbonate (VC).
[0051] In some embodiments, in the electrolyte, the content of vinylene carbonate is less than 5wt%, such as 5wt%, 4.5wt%, 4wt%, 3.5wt%, 3wt%, 2.5wt%, 2wt%, 1.5wt%, 1wt%, 0.5wt%, 0.1wt%, preferably 0.5-2wt%.
[0052] In some embodiments, the electrolyte comprises 0-15 wt % of propylene carbonate (PC), such as 15 wt %, 10 wt %, 5 wt %, 1 wt %, or 0 wt %.
[0053] Using a higher content of vinylene carbonate (VC) can make the structure of the film formed on the surface of the negative electrode active material particles more stable, while reducing the use of propylene carbonate (PC) can also prevent it from being co-embedded into the graphite layers, inhibit the peeling of the graphite layers, and improve the cycle performance.
[0054] Vinylene carbonate and propylene carbonate were tested using a gas chromatography-mass spectrometer GC-MS, and the equipment model was Shimadzu GCMS TQ-8050NX.
[0055] In the present invention, the electrolyte further includes conventional components in the art. In some embodiments, the electrolyte further includes a non-aqueous solvent, a lithium salt and a functional additive.
[0056] In some embodiments, the non-aqueous solvent comprises carbonate and / or carboxylate.
[0057] In some embodiments, the solvent includes but is not limited to at least one of ethylene carbonate (EC), diethyl carbonate (DEC), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), methyl propionate (MP), methyl butyrate (MB), ethyl butyrate (EB), ethyl acetate (EA), propyl acetate (PA), etc.
[0058] In some embodiments, the lithium salt comprises at least one of lithium hexafluorophosphate (LiPF6), lithium difluorophosphate (LiPO2F2), lithium hexafluoroantimonate (LiSbF6), lithium hexafluoroarsenate (LiAsF6), lithium bisfluorosulfonyl imide (LiFSI), lithium bistrifluoromethylsulfonyl imide (LiTFSI), lithium trifluoromethylsulfonate, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(pentafluoroethylsulfonyl)imide, tris(trifluoromethylsulfonyl)methyllithium, or lithium bis(trifluoromethylsulfonyl)imide, lithium difluorooxalatoborate (LiDFOB), lithium difluorobisoxalatophosphate, lithium tetrafluoroborate (LiBF4), lithium bis(difluorophosphoryloxy)difluoroborate, and lithium tetrakis(difluorophosphoryloxy)borate.
[0059] The functional additives may be selected from one or more commonly used additives to further improve the cycle performance or high and low temperature performance of the battery, such as fluoroethylene carbonate (FEC), difluoroethylene carbonate (DFEC), trifluoromethylethylene carbonate (TFPC), propene sultone (PST), methylene disulfonate (MMDS), 1,3-propane sultone (PS), vinyl sulfate (DTD), divinyl sulfate (BiDTD), tetravinylsilane (TVS), tris(trimethylsilyl)borate (TMSB), hexamethyldisilazane (HMDS), fluorobenzene (FB), triphenyl phosphite (TPPi), pentafluoroethoxycyclotriphosphazene (PFPN), etc. At least one of the above.
[0060] In some embodiments, the non-aqueous solvent accounts for 50wt%-80wt% of the total mass of the electrolyte, for example, 50wt%, 55wt%, 60wt%, 65wt%, 70wt%, 75wt%, or 80wt%.
[0061] In some embodiments, the lithium salt accounts for 12wt%-25wt% of the total mass of the electrolyte, for example, it can be 12wt%, 13wt%, 14wt%, 15wt%, 16wt%, 17wt%, 18wt%, 19wt%, 20wt%, 21wt%, 22wt%, 23wt%, 24wt%, or 25wt%.
[0062] In some embodiments, the added amount of the functional additive is 8wt%-25wt% of the total mass of the electrolyte, for example, it can be 8wt%, 9wt%, 10wt%, 11wt%, 12wt%, 13wt%, 14wt%, 15wt%, 16wt%, 17wt%, 18wt%, 19wt%, 20wt%, 21wt%, 22wt%, 23wt%, 24wt%, 25wt%.
[0063] In some embodiments, the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer located on at least one side of the positive electrode current collector, the positive electrode active material layer contains a positive electrode active material, and the positive electrode active material includes one or more of lithium nickel oxide, lithium titanate, lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium iron phosphate, and lithium manganese oxide.
[0064] In some embodiments, the positive electrode active material includes LiNi x Co y Mn 1-x-y O2, 0.5≤x≤0.98 (for example, 0.5, 0.6, 0.7, 0.8, 0.9, 0.95, 0.98), 0.01≤y≤0.3 (for example, 0.01, 0.05, 0.1, 0.2, 0.3).
[0065] Thermo Scientific TM iCAP TM PRO XPICP-OES Inductively Coupled Plasma Optical Emission Spectrometer Test.
[0066] In some embodiments, the positive electrode sheet further includes a positive electrode conductor, the positive electrode conductor includes at least one of single-walled carbon nanotubes and multi-walled carbon nanotubes. The positive electrode sheet further includes a positive electrode binder, the positive electrode binder may include a binder conventionally used in the art, for example, at least one of polyvinylidene fluoride, sodium carboxymethyl cellulose, styrene-butadiene rubber, polytetrafluoroethylene and polyethylene oxide.
[0067] In the present invention, based on the total mass of the positive electrode active material layer, the content of the positive electrode active material is 80%-99.8% (for example, 80%, 82%, 84%, 86%, 88%, 90%, 92%, 94%, 96%, 98%, 99% or 99.8%), the content of the positive electrode conductor is 0.1%-10% (for example, 10%, 9%, 8%, 7%, 6%, 5%, 4%, 3%, 2%, 1%, 0.5% or 0.1%), and the content of the positive electrode binder is 0.1%-10% (for example, 10%, 9%, 8%, 7%, 6%, 5%, 4%, 3%, 2%, 1%, 0.5% or 0.1%).
[0068] In some embodiments, the positive electrode current collector may be a positive electrode current collector conventionally used in the art, such as aluminum foil or a composite current collector.
[0069] The separator can be any conventional type in the art. In some embodiments, the base film is made of polyolefin, more preferably polypropylene and / or polyethylene. The separator can be commercially available.
[0070] The type of the lithium-ion battery is not limited, and it can be a cylindrical steel-shell battery, a button battery, a square aluminum-shell battery, or a soft-pack battery.
[0071] In some embodiments, the lithium-ion battery is a cylindrical steel-shell battery. It has a high volume energy density, high volume space utilization, and a negative electrode winding design that can suppress the thickness expansion of the negative electrode during charging, thereby improving the battery cycle performance. The size of the cylindrical steel-shell battery can include a diameter range of 10-50 mm and a height of 40-150 mm.
[0072] In some embodiments, the button cell capacity of the negative electrode active material is 350-370 mAh / g, and the first charge and discharge efficiency is 93-96%. The button cell assembly process is as follows: the prepared negative electrode active material and conductive carbon black, CMC, and SBR are mixed in a mass ratio of 95.5:1.5:1.5:1.5 to prepare a negative electrode slurry, and the negative electrode current collector is copper foil with a coating surface density of 10 mg / cm 2 , the designed compaction density is 1.40g / cm 3 , using lithium sheet as positive electrode, polyethylene diaphragm as separator, electrolyte containing 1mol / LLiPF6, solvent is EC / DMC / EMC volume ratio of 1:1:1 solution, assembled into button battery, battery model is CR2430. Use ArbinBT2000 battery tester for battery charge and discharge test, set the charge and discharge range to 0V~2.0V. Button battery gram capacity and first charge and discharge efficiency test: The assembled negative electrode button battery is charged and discharged according to the following steps: stand for 10min; discharge the button battery at a current density of 0.6mA, the cut-off voltage is 5mV, and record its capacity Q1; stand for 10min; discharge the button battery at a current density of 0.1mA, the cut-off voltage is 5mV, and record its capacity Q2; stand for 10min; charge the button battery at a current density of 0.6mA, the cut-off voltage is 2V, and record its capacity Q3. The button cell gram capacity of the negative electrode active material is Q3 divided by the mass of the negative electrode active material in the button cell negative electrode sheet; the first charge and discharge efficiency of the negative electrode active material is Q3 / (Q1+Q2).
[0073] In the present invention, the problem of poor cycle performance of natural graphite as negative electrode active material can be further improved through the design of negative electrode active material, negative electrode sheet and lithium ion battery system, so that the lithium ion battery has higher energy density and better charge and discharge cycle performance.
[0074] If not otherwise specified, other options for the lithium-ion battery are conventional options in the art. The battery can be assembled in a conventional manner in the art.
[0075] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0076] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.
[0077] The present invention is described in detail below in conjunction with specific embodiments, which are used to understand but not to limit the present invention.
[0078] Preparation Example
[0079] This preparation example is used to illustrate the preparation method of graphite particles.
[0080] The natural flake graphite is crushed and spheroidized to obtain a spherical graphite raw material with a certain particle size distribution, and then subjected to acid washing and purification to obtain a natural graphite raw material. The natural graphite raw material is fully mixed with the crushed asphalt according to a designed ratio, and then loaded into a graphite dry crucible for carbonization at a carbonization temperature of 900 to 1500°C. After the material is cooled, it is fully mixed, screened and demagnetized to obtain a natural graphite negative electrode active material.
[0081] Example 1-Example 11 and Comparative Example 1-Comparative Example 4
[0082] The graphite particles prepared in the preparation example were used as negative electrode active materials to prepare button cells and cylindrical steel shell batteries, respectively. The property parameters of the graphite particles are shown in Table 1.
[0083] Table 1
[0084]
[0085]
[0086] (1) Button battery
[0087] The prepared negative electrode active material and conductive carbon black, CMC, and SBR were mixed in a mass ratio of 95.5:1.5:1.5:1.5 to prepare a negative electrode slurry. The negative electrode current collector was copper foil with a coating surface density of 10 mg / cm 2 , the designed compaction density is 1.40g / cm 3 , using lithium sheet as positive electrode, polyethylene diaphragm as separator, electrolyte containing 1mol / L LiPF6, solvent is EC / DMC / EMC solution with volume ratio of 1:1:1, assembled into button cell, battery model is CR2430. Use ArbinBT2000 battery tester to perform battery charge and discharge test, set the charge and discharge range to 0V~2.0V.
[0088] The assembled negative electrode button cell was charged and discharged according to the following steps: let it stand for 10 minutes; discharge the button cell at a current density of 0.6mA, with a cut-off voltage of 5mV, and record its capacity Q1; let it stand for 10 minutes; discharge the button cell at a current density of 0.1mA, with a cut-off voltage of 5mV, and record its capacity Q2; let it stand for 10 minutes; charge the button cell at a current density of 0.6mA, with a cut-off voltage of 2V, and record its capacity Q3. The button cell gram capacity of the negative active material is Q3 divided by the mass of the negative active material in the button cell negative electrode sheet; the first charge and discharge efficiency of the negative active material is Q3 / (Q1+Q2).
[0089] It has been determined that, except for the button batteries in Example 4, Example 7, Example 9 and Example 10, whose gram capacities are respectively within the range of 340-350 mAh / g (excluding 350 mAh / g) and whose first charge and discharge efficiencies are less than 93%, the button batteries in other examples and comparative examples have gram capacities within the range of 350-370 mAh / g and first charge and discharge efficiencies within the range of 93%-96%.
[0090] (2) Cylindrical steel shell battery
[0091] Negative electrode sheet: The prepared negative electrode active material and conductive carbon black, CMC, PAA, and SBR were prepared in a mass ratio of 97.0:1.0:0.5:1.0:0.5 to prepare negative electrode slurry. A 6μm copper foil was used as the negative electrode current collector. The negative electrode slurry was evenly coated on the copper foil. The thickness of the active material layer on one side of the negative electrode sheet was 55μm, and the compaction density was 1.3g / cm 3 (The compacted density of Example 10 is 1.1 g / cm 3 ).
[0092] Positive electrode: The positive electrode active material is lithium nickel cobalt manganese oxide LiNi x Co y Mn 1-x-yO2 (x=0.83, y=0.11) was prepared by a high temperature solid phase process. The positive electrode active material: conductive agent SP: PVDF were prepared in a mass ratio of 97:1.5:1.5 to prepare a positive electrode slurry, and the positive electrode slurry was evenly coated on an aluminum foil to obtain a positive electrode sheet.
[0093] The electrolyte of the whole battery is LBC320 (purchased from Shenzhen Xinzhoubang), and the content of vinylene carbonate (VC) in the electrolyte is controlled to be 1.5wt%, and the content of propylene carbonate (PC) is controlled to be 1.6wt%. The diaphragm is a polyethylene diaphragm, and the positive electrode sheet, negative electrode sheet and diaphragm are wound to assemble the lithium battery cylindrical dry cell, and then the cylindrical steel shell battery is assembled and injected. Then the battery undergoes the formation and sorting steps to obtain a cylindrical steel shell lithium ion battery. The battery size is: the size is 43-49mm in diameter and 93-98mm in height. The battery charge and discharge test is performed using the ArbinBT2000 battery tester, and the charge and discharge interval is set to 4.20V~2.75V.
[0094] The lithium-ion battery was in a state of charge of 0% SOC. The battery was disassembled, and the negative electrode sheet was cut using an argon ion beam. The distance between the negative electrode active material layer and the negative electrode current collector (denoted as L1) and the distance between adjacent graphite particles (L2) were measured. The results are shown in Table 2. Negative electrode sheet D 004 / D 110 The values of and the results of the negative electrode sheet peel strength are shown in Table 2. Figure 1 Shown is a SEM image of the cross section of the negative electrode sheet of the lithium ion battery prepared in Example 1.
[0095] The prepared cylindrical steel shell lithium ion battery was subjected to performance testing. The testing method is as follows. The test results are shown in Table 2.
[0096] A. High temperature charge and discharge cycle performance test
[0097] (1) The cylindrical steel shell battery was placed in a 25℃ environment for 1 hour; (2) The battery was charged to 4.20V at a current density of 0.33C, and then constant voltage charging was performed with a cut-off current of 0.05C; (3) It was allowed to stand for 30 minutes; (4) The battery was discharged to 2.75V at a current density of 0.33C; (5) It was allowed to stand for 30 minutes; (6) The cylindrical steel shell battery was placed in a 45℃ environment for 4 hours; (7) The battery was charged to 4.20V at a current density of 2C. V, then constant voltage charging with a cutoff current of 0.05C; (8) standing for 30 min; (8) discharging the battery to 2.75 V at a current density of 2C; (10) standing for 30 min; (11) repeating the test steps (7) to (10) until 500 charge and discharge cycles, with the discharge capacity of the first cycle being C1 and the discharge capacity of the 500th cycle being C2. The capacity retention rate of the battery after 500 cycles at 45°C 2C / 2C is C2 / C1*100%. Figure 2 Shown is a graph of the capacity retention rate of the cylindrical steel shell battery prepared in Example 1 after 500 high-temperature cycles.
[0098] B. High rate discharge performance test
[0099] (1) The assembled cylindrical steel shell battery was placed in an environment of 25°C for 1 hour; (2) The battery was charged to 4.20V at a current density of 0.33C, and then charged at a constant voltage with a cut-off current of 0.05C; (3) It was allowed to stand for 30 minutes; (4) The battery was discharged to 2.75V at a current density of 0.33C, and the discharge capacity was recorded as A1; (5) It was allowed to stand for 30 minutes; (6) The battery was charged to 4.20V at a current density of 0.33C, and then charged at a constant voltage with a cut-off current of 0.05C; (7) It was allowed to stand for 30 minutes; (8) The battery was discharged to 2.75V at a current density of 10C, and the discharge capacity was recorded as A2.
[0100] The 10C rate discharge capacity retention rate is A2 / A1*100%.
[0101] Table 2
[0102]
[0103]
[0104] Example 12
[0105] The method described in Example 1 was followed, except that the cylindrical steel shell battery was replaced with a square aluminum shell battery, the size of which was 71 mm thick, 173 mm wide, and 207 mm long. The data of the capacity retention rate of L1, L2, 45°C 2C / 2C cycles for 500 times, and the capacity retention rate of 10C rate discharge are shown in Table 3.
[0106] Examples 13-16
[0107] A cylindrical steel shell battery was prepared according to the method described in Example 1, except that the contents of VC and PC in the electrolyte were different, as shown in Table 3. The capacity retention rates of L1, L2, 45°C 2C / 2C cycles for 500 times and 10C rate discharge capacity retention rates are shown in Table 3.
[0108] Table 3
[0109]
[0110] It can be seen from the above results that, at the level of negative active materials, by adjusting the particle size distribution, sphericity, oil absorption value and La value of natural graphite, the active material can maintain low expansion during charging; at the level of negative electrode sheet design, reducing the pore size on the negative electrode cross section and the distance between the graphite particles and the current collector and improving the peeling strength between the negative active material and the current collector can enhance the stability of natural graphite during the charge and discharge cycle; at the level of battery system design, using a cylindrical steel shell battery design and adjusting the content of vinylene carbonate and propylene carbonate in the electrolyte can make the film formation process of natural graphite more stable and inhibit the interlayer peeling and charge and discharge cycle expansion of natural graphite in subsequent charge and discharge cycles. The scheme described in the present invention can make natural graphite materials perform better in lithium-ion batteries, so it has a relatively broad application field.
[0111] It should be noted that, in this article, the terms "comprise", "include" or any other variant thereof are intended to cover non-exclusive inclusion, so that the process, method, article or device including a series of elements includes not only those elements, but also includes other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise one..." do not exclude the presence of other identical elements in the process, method, article or device including the element. In addition, it should be pointed out that the scope of the methods and devices in the embodiments of the present application is not limited to performing functions in the order shown or discussed, and may also include performing functions in a substantially simultaneous manner or in reverse order according to the functions involved, for example, the described method may be performed in an order different from that described, and various steps may also be added, omitted, or combined. In addition, the features described with reference to certain examples may be combined in other examples.
[0112] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A lithium ion battery, characterized in that: The lithium-ion battery comprises a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer located on at least one side of the negative electrode current collector, wherein the negative electrode active material layer comprises a negative electrode active material, and the negative electrode active material comprises graphite particles; When the lithium-ion battery is in a charged state of 0% SOC, the distance between the negative electrode active material layer and the negative electrode current collector is less than 0.5 μm, and the distance between adjacent graphite particles is less than 2 μm.
2. The lithium-ion battery according to claim 1, characterized in that The peak intensity ratio of Id to Ig of the negative electrode active material is Id / Ig of 0.1-0.5; and / or The graphitization degree of the negative electrode active material is 94.5%-98.5%, and / or The average length La of the growth of the crystallites of the negative electrode active material in the a-axis direction is 3. The lithium ion battery according to claim 1 or 2, characterized in that: The particle size Dv50 of the negative electrode active material is 5-25 μm, 0.35≤Dv10 / Dv90≤0.45, and Dn10≥3 μm, and / or The BET specific surface area of the negative electrode active material is 2-8 m 2 / g, and / or The tap density of the negative electrode active material is 0.9-1.2 g / cm 3 .
4. The lithium ion battery according to any one of claims 1 to 3, characterized in that: The negative electrode active material has a sphericity of 0.5-0.95 and an oil absorption value of 10-40 ml / 100 g.
5. The lithium ion battery according to any one of claims 1 to 4, characterized in that: The graphite particles include natural graphite and amorphous carbon coated on the surface of the natural graphite; Preferably, in the negative electrode active material, the content of amorphous carbon is 1-10 wt %, more preferably 3-7 wt %.
6. The lithium ion battery according to any one of claims 1 to 5, characterized in that: The compaction density of the negative electrode sheet is 1.1-1.5 g / cm 3 , and / or In the XRD pattern of the negative electrode sheet, the (004) crystal plane diffraction peak intensity D 004 The diffraction peak intensity D 110 Ratio D 004 / D 110 7-25.
7. The lithium ion battery according to any one of claims 1 to 6, characterized in that: The peel strength of the negative electrode sheet is 10-25 N / m, and / or The thickness of the negative electrode active material layer is 30-100 μm.
8. The lithium ion battery according to any one of claims 1 to 7, characterized in that: The electrolyte includes vinylene carbonate; Preferably, in the electrolyte, the content of vinylene carbonate is less than 5wt%, more preferably 0.5-2wt%; And / or, the electrolyte contains 0-15 wt % of propylene carbonate.
9. The lithium ion battery according to any one of claims 1 to 8, characterized in that: The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer located on at least one side of the positive electrode current collector, the positive electrode active material layer contains a positive electrode active material, and the positive electrode active material includes one or more of lithium nickel oxide, lithium titanate, lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium iron phosphate, and lithium manganese oxide.
10. The lithium ion battery according to any one of claims 1 to 9, characterized in that: The positive electrode active material includes LiNi x Co y Mn 1-x-y O2, 0.5≤x≤0.98, 0.01≤y≤0.3.
Citation Information
Cited By
Lithium ion battery and power utilization device
CN121237855A
A lithium ion battery, a power consuming device
CN121237855B